2022
DOI: 10.1038/s41598-022-25832-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposome approach for identifying modifiable factors for the prevention of colorectal cancer

Abstract: Previous studies have shown certain exposure factors (such as lifestyle and metabolism) are associated with colorectal cancer (CRC) events. However, the application of the exposome theoretical frame and the extent to which the exposome domain can modulate the risk of CRC remain unknown. Our study aimed to construct valid exposome measurements and examine the relationship between exposome counts and the risk of CRC. This study included 335,370 individuals in the UK Biobank. We used exploratory factor analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It is well established that even if two patients have the same tumor with the same histology, they will respond differently to treatment and have distinct oncological histories. This is particularly true for CRC patients due to various tumoral genesis processes, some of which may be partially mediated by the patient’s unique exposome [ 11 ]; interpatient heterogeneity underlies this concept. In this review, we focus instead on intrapatient heterogeneity.…”
Section: Assessing Tumoral Heterogeneity and Clonal Evolutionmentioning
confidence: 99%
“…It is well established that even if two patients have the same tumor with the same histology, they will respond differently to treatment and have distinct oncological histories. This is particularly true for CRC patients due to various tumoral genesis processes, some of which may be partially mediated by the patient’s unique exposome [ 11 ]; interpatient heterogeneity underlies this concept. In this review, we focus instead on intrapatient heterogeneity.…”
Section: Assessing Tumoral Heterogeneity and Clonal Evolutionmentioning
confidence: 99%
“…A study on pancreatic cancer suggested that several exposome factors were related to pancreatic cancer alone and in combination with other exposures [ 20 ]. A recent study by Chen et al reported that lifestyle, social and ecosystem domains are related to CRC events and incidence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%